2018
DOI: 10.1007/s10943-018-0629-8
|View full text |Cite
|
Sign up to set email alerts
|

Religion and Suicide: New Findings

Abstract: Suicide rates and risk and protective factors vary across religions. There has been a significant increase in research in the area of religion and suicide since the article, "Religion and Suicide," reviewed these issues in 2009. This current article provides an updated review of the research since the original article was published. PsycINFO, MEDLINE, SocINDEX, and CINAHL databases were searched for articles on religion and suicide published between 2008 and 2017. Epidemiological data on suicidality and risk a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
87
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(96 citation statements)
references
References 129 publications
2
87
0
4
Order By: Relevance
“…first year of college, marital status, family relationships, adolescence, among others, have been found to be associated with increased odds and/or risk factors of suicidal behaviour (Aranmolate, Bogan, Hoard, & Mawson, 2017;Engin, Gurkan, Dulgerler, & Arabaci, 2009;Eshun, 2003;Fox et al, 2018;Hawton, Saunders, & O'Connor, 2012;Mortier, Auerbach, Alonso, Axinn et al, 2018;Mortier, Auerbach, Alonso, Bantjes et al, 2018;Mortier et al, 2017Mortier et al, ,2015Tyssen, Vaglum, Grønvold, & Ekeberg, 2001). Some studies have shown religious involvement, being married and having supportive social connections (Colucci & Martin, 2008;Gearing & Alonzo, 2018;Milner et al, 2015) to be associated with reduced odds of suicidal behaviour and/or as protective factors against suicide ideation and attempts. However, in the present study, besides estimating the prevalence of suicidal behaviour, it is aimed to explore Ten response options were provided under ethnic groups; however, each of six options had frequencies <5, hence were grouped into an "other" category.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…first year of college, marital status, family relationships, adolescence, among others, have been found to be associated with increased odds and/or risk factors of suicidal behaviour (Aranmolate, Bogan, Hoard, & Mawson, 2017;Engin, Gurkan, Dulgerler, & Arabaci, 2009;Eshun, 2003;Fox et al, 2018;Hawton, Saunders, & O'Connor, 2012;Mortier, Auerbach, Alonso, Axinn et al, 2018;Mortier, Auerbach, Alonso, Bantjes et al, 2018;Mortier et al, 2017Mortier et al, ,2015Tyssen, Vaglum, Grønvold, & Ekeberg, 2001). Some studies have shown religious involvement, being married and having supportive social connections (Colucci & Martin, 2008;Gearing & Alonzo, 2018;Milner et al, 2015) to be associated with reduced odds of suicidal behaviour and/or as protective factors against suicide ideation and attempts. However, in the present study, besides estimating the prevalence of suicidal behaviour, it is aimed to explore Ten response options were provided under ethnic groups; however, each of six options had frequencies <5, hence were grouped into an "other" category.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Socio‐demographic factors such as non‐heterosexual orientation, female gender, low socio‐economic status, first year of college, marital status, family relationships, adolescence, among others, have been found to be associated with increased odds and/or risk factors of suicidal behaviour (Aranmolate, Bogan, Hoard, & Mawson, ; Engin, Gurkan, Dulgerler, & Arabaci, ; Eshun, ; Fox et al, ; Hawton, Saunders, & O'Connor, ; Mortier, Auerbach, Alonso, Axinn et al, ; Mortier, Auerbach, Alonso, Bantjes et al, ; Mortier, Cuijpers et al, ; Mortier et al, ,; Tyssen, Vaglum, Grønvold, & Ekeberg, ). Some studies have shown religious involvement, being married and having supportive social connections (Colucci & Martin, ; Gearing & Alonzo, ; Milner et al, ) to be associated with reduced odds of suicidal behaviour and/or as protective factors against suicide ideation and attempts. However, in the present study, besides estimating the prevalence of suicidal behaviour, it is aimed to explore the associations between some socio‐demographic factors (i.e., age, gender, religious groups, ethnic groups, romantic relationship status, sexual orientation, marital status, year of study, programme of study, school residential status and truancy) and suicidal behaviour risk among nursing and midwifery college students in Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…Our draft model, instead, is a reflection of the understandings of the participants in our model-building workshop, intended to apply broadly to the general population of Canada and incorporates risk and protective factors, based on the social determinants of health, at multiple levels. At the level of the individual, intersecting factors such as gender, religion, disability, and culture which may increase risk or provide protection through a variety of pathways are included [42][43][44][45]. At the level of the family, research has indicated, for example, that family connectedness is a strong predictor of positive mental health outcomes among transgender youth [46], while child maltreatment is associated with adolescent suicidal behaviours [47].…”
Section: Discussionmentioning
confidence: 99%
“…Monastics may experience lifestyle factors that put them more at risk for depression, a possibility that warrants further inquiry. Large bodies of research have found that education (48,49) and religiosity (50,51) are protective against depression, which would suggest that monastics may be relatively buffered from experiencing depression. However, another study of Tibetan refugees living in India found lower prevalence of depression and importantly found no association between monastic status or educational variables and depression levels (52).…”
Section: Discussionmentioning
confidence: 99%